Management education for contemporary challenges: the role of business school - Mamun, Mohammed Abdullah; Mohamad, Ariffin (EuroJournals Publishing, Inc., 2009)
Corporations, now a day, face pressures from different stakeholders of the business environment The changes in the environment have created threats to all of today's organizations. So, the managers have to look for finding the best possible ways of striking the implications brought by the changes. Mostly, it depends on better way of educating their people to convert previous knowledge and experience into today's competencies required for best possible strategies. This research is an attempt to understand the changing need of management expertise to face the contemporary challenges of management and the roles of business school in this concern. The business has to know the implications of the changes and accordingly has to prepare the people by their capabilities required to implement the strategies. Today, the corporations want to give a clear message to the business school about their role to play in this regard, means to put all necessary efforts to come with proper set of management skills of the challenges to be faced by the corporations. The leading business schools of the USA and Asia Pacific have got proven records of maintaining standards in terms of vision, program design and offerings. It implies that the business school has to cope into the needs of changing situations to produce future managers with all the required skills.